Contribution to the knowledge of Tegenaria domestica (Clerck, 1757) (Araneae: Agelenidae) in Southern Patagonia - Eduardo I. Faúndez; Máriom A. Carvajal; Natalia Asplanato; Flavia Raffo; Catalina J. Vargas (My University, 2019)
The presence of the spider Tegenaria domestica in southern Patagonia is revised and analyzed. New records are provided from Santa Cruz and Tierra del Fuego Province Argentina, and its presence is confirmed in Magallanes Region, Chile. The significance of the historical records and the new ones is discussed. Illustrations are provided to correctly identify the species.
Keywords: None